A Design Challenge for Transforming Justice. Issue 1 (2nd January 2022) - Bley, Kallista; Caldwell, Kela; Kelly, Meghan; Loyd, Jenna; Roth, Robert E.; Anderson, Tanya M.; Bonds, Anne; Plevin, Jenny; Madison, Darrin; Spencer, Christofer; Sims, Trevonna; Archuleta, Chris; et al.
Abstract : Transforming Justice is a collaborative project that aims to challenge the dominant narratives of policing and segregation in Milwaukee through community workshops, visual arts and storytelling, and experimental mapping. This Practices and Curations contribution describes one of the project's collaborations, a design challenge, that aimed to create and imagine new ways of visualizing (in)justice and place in Milwaukee. Engaging feminist principles of supporting multiple perspectives, the curation comprises visuals and narratives from four of the groups that participated, using their own voices and emotional tenor to describe their design processes. Working toward abolitionist design, we conclude with reflections on (1) embracing pluralism and enabling multiple design processes, (2) centering authorship and ownership, (3) exposing and contesting dominant narratives, (4) exploring dynamic and relational visual representations, and (5) incorporating tangible materials for inclusive design.